KUALITAS LAYANAN MOBILE BANKING DALAM TINJAUAN HUKUM POSITIF DAN HUKUM ISLAM: Studi Kasus di Bank BJB Syariah KCP. Patrol Indramayu - Hendy Widiyanto; Irvan Iswandi (Jurnal Penelitian Multidisiplin Ilmu, 2022)
This study is a study of the influence of the quality of mobile banking services on the BJB Syariah Bank based on the level of customer satisfaction in the perspective of positive law and Islamic law. The purpose of this study is to look at the effect of the quality of mobile banking services on the level of customer satisfaction in perspective of positive law and Islamic law. This can be seen from tangible, the relibiality, responsivitness, assurance, and empaty. This study uses primary data by conducting interviews and distributing questionnaires, and secondary data that is with books, documents and related literature that have relevance that support research. This research uses a quantitative approach. The discussion of the results of the study used a descriptive analysis approach in which the author took a sample of 33 Islamic bank bjb customers. The sampling technique used in this study is a non probability sampling technique using snowball sampling technique that selects respondents through a rolling process from one respondent to another. While the hypothesis test uses the Determinant Coefficient (R) test and the T Test while the data analysis technique uses multiple linear regression analysis methods. The test results show that there is significant effect between mobile banking services and customer satisfaction in the perspective of positive law and Islamic law.